PENGARUH VIDEO ADVERTISING TERHADAP MINAT BELI KONSUMEN - Sabrina Allysa Syam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
One form of advertising is video advertising which is an attractive marketing strategy and is more ogled by advertisers than other marketing strategies because video advertising or video advertising has audio-visual elements to convey key selling points and build a brand image for consumers or customers. This study aims to determine whether video advertising is proven to have an influence on consumer buying interest. The independent variable (X) in this study is video advertising with indicators of informativeness, entertainment, and irritation which is tested for its effect on the dependent variable (Y), namely the buying interest of consumers who have watched the video advertising